Tooling up for Mass Repression: The Subversive Activities Control Board - Frantz, Laurent B.
1953-12-12 035-0019-008 never be cited but will hesitate to take any stand which might involve the slightest risk. The threat, even if unspoken, to complain to the Attorney General may give right-wing minorities in many organizations a virtual power of veto over the majority's program. Power to tame and control voluntary associations necessarily includes power to tame and control unions—the act says "any organizations." Indeed, for many reasons—Communist enthusiasm for labor militancy, a corresponding lack of enthusiasm in reactionary groups, the ease with which strike action can be decried as tending to aid the enemy in the cold war—unions are especially susceptible to this type of attack. Although the Subversive Activities Control Board could probably order a union to register as a "Communist front" under the present act, bills to give it even more drastic and lethal powers over unions are waiting in the Congressional hopper. (See my discussion of the Butler bill in The Nation of November 28.) That the expansive possibilities of the principle were not entirely unintended was suggested by Representative Allen of Illinois speaking in the House in defense of the original Mundt-Nixon bill, which differed from the present provision in that the determination of facts would have been made by the Attorney General rather than by a special board: Another criticism offered to the bill is that it vests in the Attorney General the arbitrary power to prosecute, try, and judge persons violating the provisions of the bill. When I heard this objection to the bill, I was not only surprised but also mildly amused. Here are the people who have long advocated the persecution and harassment of business men through administrative processes. Here are the people who wanted to continue forever the control measures under which government bureaus would prosecute, try, convict, and punish business men. These people who wanted to see the free-enterprise system crushed and our nation's business men bankrupted through a systematic persecution under the New Deal—these people say this bill puts too much power of discretion in the Attorney General. To this objection I would say that the New Dealers who built the present administrative guillotine for business men should have remembered the fate that befell Dr. Guillotine. He learned that a knife cuts both ways—and now the New Dealers are being taught the same lesson. Attorney General Brownell has sole power to determine what organizations shall be charged before the board. The length to which he may be expected to push Mr. Dies's formula is shown not only by the charges incorporated in his first "front" petitions but also by his recent announcement of intention to put the National Lawyers Guild on his own "subversive" list. With control of the American Bar Association in very conservative hands, the Lawyers Guild is virtually the only vehicle through which the views of liberal lawyers can be given organized expression. Mr. Brownell says that "on every major issue" in recent years the guild "has steadfastly followed the party line, and its programs and actions have been consistent with it, excepting only those issues so notorious that their espousal would too clearly demonstrate the Communist control.'' Mr. Brownell seems to have learned from Senator McCarthy that the accuser can rely on deviation and non-deviation simultaneously, the latter to show Communist control and the former to show efforts to conceal Communist control. Or, as a last resort, instances of deviation may be shrugged off as not involving a "major issue." The Lawyers Guild's membership and activities have always been open to the public, and it is not accused of promoting its ideas otherwise than by the methods of a bar association—public debate and participation in litigation. Mr. Brownell, essentially, is attacking the idea of a free and independent bar. There seems to be nothing in the Attorney General's record or the board's to suggest that the principle will not be expanded to the limits of its logic unless the courts or public opinion call a halt. (In what seems likely to be the key test of the act, the guild has brought suit to enjoin the hearing of the petition). If each accused organization is left to fight its solitary battle, effective resistance will become increasingly difficult. The board will be progressively strengthened by the accumulation of precedent, and the opposition will be progressively weakened by the spreading paralysis of fear. It is of the nature of this type of attack that it tends to isolate each current victim by making people afraid they may incur some associative guilt if they come to his defense. Still, it ought not to be necessary for Americans to relearn the hard way the lesson that liberty is indivisible. REPRINTS AVAILABLE Additional copies of this pamphlet, a reprint from The Nation magazine, are available at the following rates: Single copies 10c each 100 " $7.50 500 " 25.00 1000 " 45.00 Address your requests to The Nation, 333 Sixth Avenue, N.Y.C. 14, ATTN: Reprint Department. Payment must accompany each order. 292/946/35/20(vii)